the peran pendidikan keluarga dalam pengamalan nilai-nilai pancasila di kelas 5 SD Negeri 258 Aek Nangali: Metode Pendidikan dalam Menanamkan Nilai-Nilai Pancasila Faktor Pendukung dan Penghambat Pendidikan Keluarga - nanda wahyu saputra nasution; rica umrina lubis; rahmi seri hanida (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
This study aims to analyze the role of family education in improving the practice of Pancasila values in fifth-grade students of SD Negeri 258 Aek Nangali. This study uses a qualitative approach with a case study type that allows researchers to explore in depth specific phenomena in a limited context. Data collection was carried out through observation, structured interviews, and documentation involving parents, teachers, and 20 fifth-grade students as research subjects. Data analysis techniques using the Miles and Huberman model include data reduction, data presentation, and conclusion drawing. Data validity was tested through source triangulation and method triangulation to ensure the validity and reliability of the research results. The results show that: parents mostly use hiwar education methods with a percentage of 40%, habituation 20%, exemplary 45%, where parents apply communicative, religious, and contextual approaches in instilling Pancasila values; Family education in instilling Pancasila values faces complex dynamics between supporting and inhibiting factors. The main supporting factors include the active role of parents as role models, stable socio-economic conditions, parental education level, and a conducive social environment. Meanwhile, the main inhibiting factors are incorrect or negative parenting patterns, socio-economic problems, external environmental influences, psychological conditions, and family stability. This study confirms that family education plays a very significant role in shaping students' character and serves as the initial foundation for the internalization of Pancasila values. This research provides an important contribution to the development of character education strategies that involve the active role of families as school partners in creating a generation with Pancasila character.